Predictors of 3-month abstinence in smokers attending stop-smoking clinics in Malaysia - Wee, L.H.; West, R.; Bulgiba, A.M.; Shahab, L. (2011)
Introduction: Much is known about the predictors of success in quitting smoking. In particular, nicotine dependence, but not strength of motivation to stop, appears to predict abstinence. However, to date, studies have come almost exclusively from Western countries. More data are needed on the cross-cultural generalizability of these findings. Methods: One hundred and ninety-eight smokers attending 5 stop-smoking clinics in Malaysia completed a questionnaire prior to their target quit date and were followed up 3 months after this date. Predictors included sociodemographic variables, smoking patterns, past history of quitting, characteristics of current quit attempt, and smoking motives as well as nicotine dependence (Fagerstrom Test for Nicotine Dependence FTND) and self-rated strength of motivation of stop. Results: At 3-month follow-up, 35.4% (95% CI: 28.7-42.0) of participants reported being abstinent. A backward elimination multiple logistic regression identified a number of significant predictors of success, including strength of motivation to stop (adjusted odds ratio OR: 3.05, 95% CI: 1.28-7.25). FTND did not predict success. Conclusions: Motivation and nicotine dependence may play different roles in explaining variation in ability to stop smoking in different cultures.